Designing for resilience: How Futch maternity care collaborations anticipate, adapt, and thrive during a pandemic - Jennifer van den Berg; Alex A. Alblas; Pascale M. Le Blanc; A. Georges L. Romme (Administrative Sciences, 2022)
The success factors and challenges of interorganizational collaboration have been widely studied from different disciplinary perspectives. However, the role of design in making such collaborations resilient has received little attention, although deliberately designing for resilience is likely to be vital to the success of any interorganizational collaboration. This study explores the resilience of interorganizational collaboration by means of a comparative case study of Dutch maternity care providers, which have been facing major challenges due to financial cutbacks, government-enforced collaborative structures, and the recent COVID-19 pandemic. Our findings make two contributions to the literature. First, we further develop the construct of interorganizational resilience. Second, we shed light on how well-designed distributed decision-making enhances resilience, thereby making a first attempt at meeting the challenge of designing for interorganizational resilience.
Keywords: 350; health care; heterarchy; interorganizational collaboration; organizational resilience